The frictional resistance induced by bacterial based biofouling in drainage pipelines. Issue 2 (4th March 2017) - Cowle, Matthew W.; Babatunde, Akintunde O.; Bockelmann-Evans, Bettina N.
ABSTRACT: This paper aims at improving the current understanding of bacterial-based biofouling in drainage pipelines. Using a purpose built pipeline facility consisting of a high density polyethylene pipe, biofilms were incubated with synthetic wastewater for 20 days at three steady-state flow regimes. The results obtained have shown that the presence of a biofilm can cause a significant increase in frictional resistance. The magnitude of a biofilm's frictional resistance is a function of the shear conditions under which the biofilm is incubated. In particular, the lower the conditioning shear, the higher the frictional resistance imparted by the biofilm. This is attributed to the thickness and roughness distribution induced by such conditions, and it serves to highlight the problem of characterizing a biofilm's effective roughness using a single roughness scale. The study has also supported the earlier funding that the von Kármán constant is non-universal, and is dependent on Reynolds number for biofouled pipes.